1998
DOI: 10.1007/s002449900387
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Hydrocarbon Contaminants in Polar Bears from Eastern Russia, North America, Greenland, and Svalbard: Biomonitoring of Arctic Pollution

Abstract: Adipose tissue samples from polar bears (Ursus maritimus) were obtained by necropsy or biopsy between the spring of 1989 to the spring of 1993 from Wrangel Island in Russia, most of the range of the bear in North America, eastern Greenland, and Svalbard. Samples were divided into 16 regions corresponding as much as possible to known stocks or management zones. Concentrations of dieldrin (DIEL), 4,4'-DDE (DDE), sum of 16 polychlorinated biphenyl congeners (sigma PCB), and sum of 11 chlordane-related compounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(93 citation statements)
references
References 40 publications
7
82
4
Order By: Relevance
“…Furthermore, ringed seals are an important prey source for polar bears that have been shown to be the highest contaminated marine mammals. [77,81,82] Butt et al reported that mean concentrations were similar between ringed seal populations in the Canadian Arctic (11 locations, 10 liver samples per site). Concentrations of PFNA and PFUnDA generally ranged between 1 and 10 ng g À1 ww, whereas PFTriDA was less than 1 ng g À1 ww and PFOS concentrations were mainly between 10 and 40 ng g À1 ww.…”
Section: Spatial Distribution Of Pfcs In Marine Mammalsmentioning
confidence: 99%
“…Furthermore, ringed seals are an important prey source for polar bears that have been shown to be the highest contaminated marine mammals. [77,81,82] Butt et al reported that mean concentrations were similar between ringed seal populations in the Canadian Arctic (11 locations, 10 liver samples per site). Concentrations of PFNA and PFUnDA generally ranged between 1 and 10 ng g À1 ww, whereas PFTriDA was less than 1 ng g À1 ww and PFOS concentrations were mainly between 10 and 40 ng g À1 ww.…”
Section: Spatial Distribution Of Pfcs In Marine Mammalsmentioning
confidence: 99%
“…et al, 1992a;Wolkers et al, 1998 and polar bears Ž . Norstrom et al, 1998 . The lack of relationship between body length and concentrations of different OC concentrations in this study is consistent with previous Ž studies of white whales Stern et al, 1994;Muir et .…”
Section: ( )mentioning
confidence: 99%
“…Likewise, OC bur-Ž . dens in polar bears Ursus maritimus from Svalbard are higher than in their Canadian or Alaskan Ž counterparts Norheim et al, 1992;Kleivane et al, 1994;Bernhoft et al, 1997;Norstrom et al, . 1998 .…”
Section: Introductionmentioning
confidence: 98%
“…as recently reviewed by Braune et al (2005-this issue) the polar bear serves as an ideal sentinel species for biomonitoring spatial and temporal trends of CHCs, such as chlordane (CHL)-related compounds and polychlorinated biphenyls (PCBs), as a result of its wide distribution throughout the Arctic and Subarctic and its key role as apex predator in the marine environment (de March et al, 1998;Muir et al, 1999;Muir and Norstrom, 2000;Fisk et al, 2003;AMAP, 2004). As described in Norstrom et al (1998), there are discrete populations of polar bears in the Canadian Arctic. Combined with knowledge of sea ice and land barriers, 12 polar bear management zones were defined.…”
Section: Introductionmentioning
confidence: 99%